GLOBALIZATION OF HIGHER EDUCATION: IMPLICATIONS FOR INDIA - R. VENKATESH (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Globalization has had a significant impact on higher education in India, with the influx of international students, faculty, and collaborations with foreign universities. This paper explores the implications of globalization on higher education in India, including the challenges and opportunities it presents. The paper discusses how globalization has led to increased competition, changes in curriculum and teaching methods, and the need for higher education institutions to adapt to the changing landscape. The paper also highlights the benefits of globalization, such as the exposure to different cultures and ideas, and the potential for knowledge sharing and collaboration. The paper concludes by suggesting ways in which India can leverage the opportunities presented by globalization and mitigate its challenges.